Filamentous fungi as promising agents for the biodegradation of biosolids compounds - Naves, Laiza Rosa; Da Silva, Lucas Leonardo; Da Cunha, Elida Lucia; De Almeida, Verediana Fiorentin Rosa; De Sá, Antônio Sérgio Ferreira; Sena, Brenda Letícia; Moreira, Izabel Cristina; Dos Santos, Solange Xavier [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2019)
Wastewater Treatment Plant (WWTP) generate pasty wastes, known biosolids, which can be toxic and recalcitrant, motivating studies aiming at their degradation. Filamentous fungi were investigated to degradation of biosolids from a WWTP in the Goiânia, Goiás, Brazil. All grew in the presence of biosolids, being inhibited by increase in concentration, except SXS629, which increased proportionally to the concentration. All grew in the middle with biosolids at the original pH (10.5), although the correction (6.8) provided higher growth. Except SXS90, the others (SXS37, SXS615 and SXS628) degraded the biosolid, growing in medium containing biosolids as the only source of carbon; highlighting SXS628, whose growth in the biosolids exceeded the control. All evaluated isolates synthesize at least two prospected enzymes, especially SXS630 and SXS634, which synthesize all (carboxymethyl cellulase, tannase, polyphenoloxidase). This shows the potential use of these isolates (combined or not) in biotechnological processes aiming at the degradation of biosolids, especially SXS37.
Keywords: Activated Sludge; Bioremediation; Goiânia; Wastewater Treatment